Answer: A(3, -5)
B(6, -2)
C(9, -2)
Explanation:
If we have a point (x, y), and we do a reflection over the axis y = a, then the only thing that will change in our point is the value of x.
Now, the distance between x and a must remain constant before and after the reflection.
so if x - a = d
then the new position of the point will be:
(a - d, y) = (2a - x, y).
I will use that relationship for the 3 points
A)
We start with the point (1, -5)
The reflection over y = -1 leaves.
The distance between 1 and -1 is = 1 - (-1) = 2.
Then the new point is (-1 - 2, -5) = (-3, -5)
Now we do a reflection over y = 1, so D = -3 - 1 = -2
Then the new point is:
A = (1 -(-2), -5) = (3, -5)
B) (2, -2)
Reflection over y = -1.
distance, d = 2 - (-1) = 3
the point is (-1 - 3, -2) = (-4, -2)
Now, a reflection over y = 1.
The distance is D = -4 - 1 = -5
The new point is (1 - (-5), 2) = (6, -2)
C) (5, -2)
reflection over y = -1
Distance: D = 5 - ( - 1) = 6
New point: (-1 - 6, -2) = (-7, -2)
Reflection over y = 1.
Distance D = -7 - 1 = -8
New point ( 1 - (-8), -2) = (9, -2)